TRANSFORMASI BUDAYA DARI KHILAFAH TURKI UTSMANI MENUJU REPUBLIK TURKI MODERN (1830-1950) - Sri Mulyati (Arabic Literature Department, 2014)
This study analyzed the problem about the phenomenon of cultural transformationin Turkey. (1) to explain the process of cultural transformation on the system ofgovernment and politics and religion from the Ottoman Empire until the modern ofRepublic Turkey. (2) to explains how the forms of changes to the Turkey culture, with thefactors that become the cause a process of cultural transformation that is a process ofrenewal and change in Turkey to the modern age. Along with the problems of the research objectives above, this research wasconducted by applying library research. The process of analysis in this study usesqualitative analysis inductive. techniques of data collection in this study is the observation techniques and analysis of documents. Analysis of the data in this study using an interactive model of analysis, that is data reduction, data display and conclusion drawing. Based on the result of this research, it can be concluded that the process of culturaltransformation in Turkey is caused that; (1) the influx of outside culture for changingvalues because the process of global and universal communications; (2) internal creativity that forming intellectual innovation with the new discoveries; (3) the pressures and influences from outside, from the West and Europe; and (4) change of the form of renewal, reform and transformation. Politics, culture and religion be an important factor in the effort to change process in Turkey. Transformation of culture in Turkey contains three basic concepts of mind, that is analytical, historical, and practical.